Peran Guru Pendidikan Agama Islam Dalam Meningkatkan Minat Dan Prestasi Belajar Pendidikan Agama Islam Siswa Di MTs Muhammadiyah Surakarta Dan Smp Ta'mirul Islam SurakartaTahun Pelajaran 2016/2017 - Ramdhani, Deddy, Prof. Dr. Bambang Sumardjoko, Dr. Mohamad Ali, M.Pd (2017)
The background of this research is that teachers have an important role in education, the role of Islamic religious education teachers are very large contributionin the implementation of the learning process, at least will shape the attitudes of students in learning. The purpose of this study was to describe the role of the teacher of Islamic education, the difficulties are faced by teachers of Islamic religious education in carrying out its role, the efforts of teachers of Islamic religious education to overcome difficulties in carrying out its role to encourage and increase learning achievement of Islamic religious education of students in MTs Muhammadiyah Surakarta and junior hight school Ta' mirul Islam Surakarta. This research type is field research with qualitative descriptive analysis, and wearing a phenomenological approach. Data were collected by interview, observation and documentation. The results showed that the First: the role of teachers of Islamic education at the two schools are generally don't have significant difference among them is the role of the teacher from the education of Islam as a motivator, mentor, educator, demostrator, manager classes, mediator, facilitator , organizer, supervisor, evaluator. Second: The difficulties are faced by the Islamic religious education teachers in carrying out its role to encourage and increase learning achievement of Islamic religious education students at both schools is caused by several factors, the first factor of the average family cooperation with the school under the supervision of student learning at home. School factors, both schools have teachers who have not been able to maximize the school's facilities are perfect in learning, infrastructures and facilities at MTs Muhammadiyah Surakarta inadequate while in junior hight school Ta'mirul Islam Surakarta is sufficient. Student factors are unruly, stubborn and rebellious they are abundanted at MTs Muhammadiyah Surakarta, whereas at junior hight school Ta'mirul Islam Surakarta already held a screening process of new students so that it is rare. Third: The efforts made the teacher of Islamic education in overcoming the difficulty in MTs Muhammadiyah Surakarta and junior hight school Ta'mirul Islam Surakarta is to do a variety of ways including i.e. guidance teachers such as guiding students who lack the passion and interest in learning as well as his achievements are declining and the attitude of their ways are less good, contact the student who's like a visit home students, checking and investigating the parents of students who felt their progress decreases the learning material and hard to catch , coaching teachers like follow a wide range of training, seminar, workshop, the MGMP. as well as giving rewards like praise, honour award in the form of gifts, school supplies, as for punishment such as the granting of scientific tasks i.e. memorizing short letters, Arabic vocabulary and United Kingdom and swept the school yard.